2018
DOI: 10.1093/ofid/ofy185
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes Associated With Acquisition of Daptomycin and Linezolid–Nonsusceptible Vancomycin-Resistant Enterococcus

Abstract: BackgroundVancomycin-resistant enterococcus (VRE) causes substantial health care–associated infection with increasing reports of resistance to daptomycin or linezolid. We conducted a case–control study reporting 81 cases of daptomycin and linezolid–nonsusceptible VRE (DLVRE), a resistance pattern not previously reported.MethodsWe reviewed VRE isolates from June 2010 through June 2015 for nonsusceptibility to both daptomycin (minimum inhibitory concentration [MIC] > 4) and linezolid (MIC ≥ 4). We matched cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Daptomycin resistance has been shown to arise within patients during treatment [19]. Additionally, a number of studies have reported prior daptomycin treatment as a key risk factor for infection with daptomycinresistant VR E. faecium [20][21][22], which is consistent with off-target selection. Finally, transmission of VR E. faecium is common in hospital settings, meaning resistance that arises in one patient may pose a threat to others.…”
Section: Introductionmentioning
confidence: 76%
“…Daptomycin resistance has been shown to arise within patients during treatment [19]. Additionally, a number of studies have reported prior daptomycin treatment as a key risk factor for infection with daptomycinresistant VR E. faecium [20][21][22], which is consistent with off-target selection. Finally, transmission of VR E. faecium is common in hospital settings, meaning resistance that arises in one patient may pose a threat to others.…”
Section: Introductionmentioning
confidence: 76%
“…Third, hitchhiking is also a possibility, where daptomycin resistance alleles could be carried to high frequency either due to stochastic dynamics or because they happen to be present in a clone that for unrelated reasons had a fitness advantage in the hospital setting (33). While there are no known overlaps in resistance mutations between linezolid and daptomycin (34,35), coresistance is common in some settings (36). Thus, the increased linezolid use could drive daptomycin resistance; however, an increase in linezolid resistance was not observed in this time period.…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin resistance has been shown to arise within patients during treatment [19]. Additionally, a number of studies have reported prior daptomycin treatment as a key risk factor for infection with daptomycin resistant VRE [20][21][22], which is consistent with offtarget selection. Finally, transmission of VR E. faecium is common in hospital settings, meaning resistance that arises in one patient may pose a threat to others.…”
Section: Introductionmentioning
confidence: 88%